Grid Impact Study of Lombok Power System Due to the Integration of Solar Power Plant - Azhar, Fakhrudin; Jufri, Fauzan Hanif; Garniwa, Iwa (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2025)
In recent years, the response to climate change and the need for sustainable energy have driven the global energy transition towards renewable energy, particularly Solar Power Plants (SPP). As a tropical archipelagic country with abundant solar energy potential, Indonesia is increasingly committed to integrating renewable energy into the national electricity system. However, integrating SPP also has several drawbacks to the electrical system. For instance, there is an absence of inertia in SPP because the SPP does not contain rotating machines, and the intermittency is due to SPP power production being highly dependent on the availability of sun irradiance. This research analyzes the effects of SPP penetration on the existing electrical system. Newton Raphson load flow, three-phase line-to-ground short circuit, and transient disturbance are used to investigate the impact of SPP penetration. The results show that the SPP penetration enhances the voltage steady state profile due to the additional active power from SPP. Furthermore, there are no increasing short circuits due to the characteristic of an inverter with no impedance. In addition, the transient response has an effect as SPP has no inertia. Hence, the system tends to experience swings in conditions.